Analysis of The Need for Green Open Spaces in Reducing CO2 Carbon Dioxide Emissions in the Bahteramas Hospital Area of Southeast Sulawesi Province - Aindo, Nur Rezki; Indriyani, Lies; Manan, Abdul; Gandri, La; Sahindomi Bana (University of Jember, 2023)
This study aims to determine CO2 emissions resulting from transportation sources, residents, electricity and the ability of green open spaces (RTH) to reduce CO2 gas emissions in the Bahteramas Hospital Area. This research was conducted in December 2022-January 2023 at Bahteramas Baruga Hospital, Kendari City, Southeast Sulawesi Province. The results showed that the highest CO2 emission load was generated from the use of electricity with a total of 54,119 kg/day, then population emissions were 4,933 kg/day, while the lowest emission load was generated from CO2 transportation emissions of 4,437 kg/day. The total emission generated in the Bahteramas Hospital Area is 63,489 kg /day. The ability of green open space to reduce CO2 emissions is 8,399 kg/day so that it still has residual CO2 emissions that have not been able to be absorbed by the existing green open space of 55,090 kg/ day.